Analysis Of Islamic Law On Bank Interest: Comparison Of The Concepts Of Usury And Modern Banking - Fitra Ardiansyah; Achyar Zein (AT-TAFAHUM: Journal of Law, 2021)
This study examines the concept of bank interest from the perspective of fiqh muamalah by analyzing its legal status, characteristics, and relevance within the contemporary banking system. The research employs a qualitative normative legal approach based on library research, utilizing conceptual and comparative methods. Primary sources include the Qur'an and Hadith concerning the prohibition of riba (usury), while secondary sources consist of classical and contemporary Islamic jurisprudence literature, scientific journals, and references on Islamic and conventional economics. Data were collected through literature review and analyzed descriptively and qualitatively to compare the opinions of classical and contemporary Islamic scholars regarding bank interest. The findings indicate that bank interest serves as the principal mechanism in conventional banking, functioning as compensation for deposits and charges on loans while supporting banking operations, investment, and economic growth. Nevertheless, from the perspective of classical Islamic jurisprudence, bank interest is generally regarded as a form of riba because it involves an additional payment on the principal of a loan without productive economic activity, making it prohibited under Islamic law. Contemporary scholars, however, present more diverse interpretations. While many continue to classify bank interest as prohibited, others distinguish modern bank interest from classical riba by considering its economic function, the absence of exploitation, and the principles of necessity (ḍarūrah) and public interest (maṣlaḥah). The study further reveals that the debate over bank interest extends beyond legal considerations to broader economic and social dimensions, including financial justice, inequality, and sustainable economic development. It concludes that understanding bank interest requires a contextual and comprehensive approach that balances adherence to Islamic legal principles with the realities of modern financial systems. Strengthening Islamic financial institutions is therefore recommended as a practical alternative for achieving economic justice while remaining consistent with the objectives of Sharia.